Nuclear Nestin deficiency drives tumor senescence via lamin A/C-dependent nuclear deformation - Yanan Zhang (Nature Portfolio, 2018)
Nestin can be localised in the nucleus of cancer cells, but its nuclear role in tumorigenesis is unclear. Here, the authors show that nuclear Nestin prevents senescence in tumor cells by stabilising lamin A/C from proteasomal degradation to maintain nuclear integrity.